Faktor-faktor yang Memengaruhi Keputusan Konsumen dalam Pembelian Melon Premium di Kota Bandung (Studi Kasus pada PT. Kebun Bumi Lestari) - Immanuel, Marvel Secio; Renaldi, Eddy (Universitas Galuh, 2024)
The Farmhill is a premium melon producer in Indonesia whose products are spread throughout Indonesia. When compared with the price of other melons, premium melons have a higher price. However, demand, production, and marketing of this melon remain high and even increase. This does not appear to be suitable with the law of demand which states